Enhancement Of Solubility Of Poorly Water-Soluble Drug By Solid Dispersion Method Formulation And Evaluation Of Rivoroxaban Capsule Dosage Form - P. Savant, Namrata; Kalyankar, T. M.; Shinde, Nagoji; B. Shinde, Komal; K. Kamble, Rohan; A. Patkari, Mayur; S. Patil, Varun; V. Kadam, Manjusha (Journal of Neonatal Surgery, 2024)
Rivaroxaban is an Antiplatelet/anticoagulant Drug used in the treatment of venous thromboembolism and belongs to the Biopharmaceutical classification system class II; hence it has a low solubility. So that the aim of this study is to enhance the solubility of the drug by solid dispersion method. Solid dispersion is nothing but the combination of two component one hydrophilic matrix and second hydrophobic drug. There are various methods are used for the preparation of solid dispersion in which solvent evaporation method used in the research. The solubility of rivaroxaban was increased by dissolving the different polymers with API using suitable solvent (Dichloromethane+ methanol) in three different ratios 1:0.5, 1:1, 1:1.5 and then this preparation kept for 24 hrs in Hot air oven to get solvent evaporate. The best polymer and ratio screening was done with the help of solubility study, the solubility study is done with the different buffers like Ph 6.8 phosphate buffer, 4.5 acetate buffer, 0.1N HCL, water with the help of UV spectrophotometer. The evaluation of final dosage form is done with the help of dissolution study in media 4.5 acetate buffer+ 0.2% SLS for about 2hrsat a specific time interval 10, 15, 30, 45, 60, 90, 120 minutes. Drug polymer compatibility study was done by different analysis like FTIR, XRD, DSC and SEM.